Workshop Virtual Reality bagi Guru untuk Meningkatkan Inovasi Pembelajaran pada SMK Muhammadiyah 2 Pekanbaru - Efendi, Yoyon; Nasution, Torkis; Yanti, Rini (Community Education Engagement Journal, 2023)
This community service aims to enhance learning innovation through the use of virtual reality technology for teachers at SMK Muhammadiyah 2 Pekanbaru. Through virtual reality workshops, it is hoped that participating teachers will be able to independently innovate and improve the quality of their learning and use their knowledge, test, and continue to acquire and personalise learning innovations. This workshop has the impact of enhancing the knowledge and skills of educators, especially in the field of virtual reality technology, in metaverse schools in the field of education. Metaverse is an innovation in learning practice. The participants are all 50 teachers from Muhammadiyah Vocational School 2, Pekanbaru. The activity will take place from September 29 to August 7, 2023. The material for this activity is the teacher's knowledge about dealing with millennials, the teacher's knowledge about using technology in learning, the teacher's knowledge about interactive teaching, teachers' knowledge and skills of virtual reality technology, and teachers' knowledge and skills of implementing virtual reality in learning schools. The impact that students achieve is an increase in their knowledge of virtual reality technology as a means of interactive learning in the classroom and in the laboratory. During this time, the school has become a virtual reality pilot project for super schools and has acted as a school barometer with virtual reality promotions in Pekanbaru City, Province Riau, and even across the country. The success of this workshop was measured by managing pre-deployment and post-deployment tests using the same test. After participating in this workshop, teachers' ability to apply virtual reality technology to learning increased by 40%.